2022
DOI: 10.1186/s12879-022-07412-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among GLASS pathogens in Morocco: an epidemiological scoping review

Abstract: Background Monitoring of antimicrobial resistance (AMR) is of great importance due to the frequency of strains becoming increasingly resistant to antibiotics. This review, using a public health focused approach, which aims to understand and describe the current status of AMR in Morocco in relation to WHO priority pathogens and treatment guidelines. Methods PubMed, ScienceDirect and Google Scholar Databases and grey literature are searched published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 122 publications
2
1
0
Order By: Relevance
“…However, there are also studies showing higher rates of resistance to other classes of antimicrobials -Fluoroquinolones and Cephalosporins (9,32). Regarding K. pneumoniae, this study had similar results to those from Mexico and Tanzania, where the isolates had the second highest proportion of MDR profiles, and Morocco, where in addition to MDR status an alarming rate of carbapenemase-producing strains was detected (2,29,32). The results obtained on carbapenemase production by ord.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, there are also studies showing higher rates of resistance to other classes of antimicrobials -Fluoroquinolones and Cephalosporins (9,32). Regarding K. pneumoniae, this study had similar results to those from Mexico and Tanzania, where the isolates had the second highest proportion of MDR profiles, and Morocco, where in addition to MDR status an alarming rate of carbapenemase-producing strains was detected (2,29,32). The results obtained on carbapenemase production by ord.…”
Section: Discussionsupporting
confidence: 81%
“…However, many studies focus on various aspects of AMR occurrence and "frequency" in the health system, society, and the environment. Three studies conducted in Cameroon, Morocco, and Vietnam showed Enterobacteriaceae as the most frequently isolated microorganisms, followed by S. aureus, as we determined, but Camara N. and Haeeb A. determined an opposite situation in Tanzania and Saudi Arabia (2,9,27,28,29). When analyzing isolates according to the source (biosubstrate), studies focusing on uropathogens showed that E. coli is the most frequent uropathogen followed by K. pneumoniae (in Ethiopia and USA), compared to 2 studies from Romania showing 2 distinct situations -one study showed a similar situation as in Ethiopia, and the second one showed a distinct situation -with P. aeruginosa on the first place similar to the one in Mexico (14, 25, 30 31, 32).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation